2004
DOI: 10.1104/pp.103.031740
|View full text |Cite
|
Sign up to set email alerts
|

NopL, an Effector Protein ofRhizobiumsp. NGR234, Thwarts Activation of Plant Defense Reactions

Abstract: Bacterial effector proteins delivered into eukaryotic cells via bacterial type III secretion systems are important virulence factors in plant-pathogen interactions. Type III secretion systems have been found in Rhizobium species that form symbiotic, nitrogen-fixing associations with legumes. One such bacterium, Rhizobium sp. NGR234, secretes a number of type III effectors, including nodulation outer protein L (NopL, formerly y4xL). Here, we show that expression of nopL in tobacco (Nicotiana tabacum) prevents f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
108
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(113 citation statements)
references
References 59 publications
4
108
0
1
Order By: Relevance
“…Previous studies showed that transgenic plant cells expressing the type 3 effector gene nopL of NGR234 showed effects on expression of defense genes, suggesting that NopL can suppress the innate immunity of the plant (24). These findings were consistent with the observation that a nopL mutant of NGR234 (strain NGR⍀nopL) induced fewer nodules on the legume Flemingia congesta (22).…”
supporting
confidence: 81%
See 3 more Smart Citations
“…Previous studies showed that transgenic plant cells expressing the type 3 effector gene nopL of NGR234 showed effects on expression of defense genes, suggesting that NopL can suppress the innate immunity of the plant (24). These findings were consistent with the observation that a nopL mutant of NGR234 (strain NGR⍀nopL) induced fewer nodules on the legume Flemingia congesta (22).…”
supporting
confidence: 81%
“…These findings were consistent with the observation that a nopL mutant of NGR234 (strain NGR⍀nopL) induced fewer nodules on the legume Flemingia congesta (22). Experiments with recombinant NopL protein expressed in Escherichia coli revealed that NopL could be phosphorylated at unknown sites by nondefined protein kinases from crude plant protein extracts (23,24). Phosphorylation of NopL in vitro was reduced by addition of PD98059, a MAPK kinase inhibitor (23).…”
supporting
confidence: 77%
See 2 more Smart Citations
“…Meanwhile, the T3Es NopL and NopP of NGR234 have positive effects on symbiosis with their host legumes (9). Both NopL and NopP are phosphorylated by plant protein kinases, and NopL can prevent the complete induction of pathogenesis-related defense proteins when expressed in Lotus japonicus roots (10). However, the molecular basis for T3SS-involved nodulation enhancement has not been fully elucidated.…”
mentioning
confidence: 99%